2021
DOI: 10.1021/acs.jcim.0c01320
|View full text |Cite
|
Sign up to set email alerts
|

Shedding Light on the Inhibitory Mechanisms of SARS-CoV-1/CoV-2 Spike Proteins by ACE2-Designed Peptides

Abstract: Angiotensin-converting enzyme 2 (ACE2) is the host cellular receptor that locks onto the surface spike protein of the 2002 SARS coronavirus (SARS-CoV-1) and of the novel, highly transmissible and deadly 2019 SARS-CoV-2, responsible for the COVID-19 pandemic. One strategy to avoid the virus infection is to design peptides by extracting the human ACE2 peptidase domain α1-helix, which would bind to the coronavirus surface protein, preventing the virus entry into the host cells. The natural α1-helix peptide has a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 136 publications
0
25
0
Order By: Relevance
“…Further, compound A possesses nitro-aryl features imparting the potential risk of mutagenicity due to interaction of nitro group with DNA [ 63 ]. Peptides identified by de Oliveira et al [ 30 ] and Baig et al [ 31 ] may not have sufficient oral bioavailability as compared to identified small molecules ( 1 – 17 ) due to degradation of these peptides under the acidic environment of stomach and peptidase enzymes [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, compound A possesses nitro-aryl features imparting the potential risk of mutagenicity due to interaction of nitro group with DNA [ 63 ]. Peptides identified by de Oliveira et al [ 30 ] and Baig et al [ 31 ] may not have sufficient oral bioavailability as compared to identified small molecules ( 1 – 17 ) due to degradation of these peptides under the acidic environment of stomach and peptidase enzymes [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…2 ) as potent anti-viral agent with IC 50 of 28.1 µM against vero-E6 cells incubated with SARS CoV-2 [ 29 ]. Three different peptide fragments composed of N -terminal amino acid residues of α 1 helix of ACE2 peptidase domain have been reported by de Olivera and co-workers as effective agents to inhibit the binding of SARS CoV-2 spike protein with human ACE2 as identified through molecular modelling [ 30 ]. Further, Baig et al identified the 13-amino acid peptide (FLDKFNHEAEDLF) as spike protein inhibitor with minimal inhibition (40% at 100 µM concentration) of ACE2-spike protein–protein interactions through enzyme-linked immunosorbent (ELISA)-dependent inhibitory assay [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…19,21 De novo protein design and computer-based peptide design have also been applied for engineering native soluble ACE2 to generate potential SARS-CoV-2 entry blockers. [22][23][24] These studies highlight the importance of ACE2-based therapeutics for treating COVID-19. However, whether cell therapy can be used for the delivery of ACE2-based therapeutics is unclear.…”
Section: Introductionmentioning
confidence: 93%
“…All these works were also dealing with in silico peptide modelling and screening of their binding with the RBD of the spike protein. In addition, the specificity pattern of this interaction was specified (Kuznetsov and Järv 2020b ) and the structural basis of the molecular recognition mechanism of these peptides was described (Freitas et al 2021 ). However, there is still no experimental data characterizing kinetics of interaction of these peptide fragments with the RBD on SARS-CoV-2 spike protein.…”
Section: Introductionmentioning
confidence: 99%